2016
DOI: 10.1177/1744987116650923
|View full text |Cite
|
Sign up to set email alerts
|

Researching domestic violence and abuse in healthcare settings: Challenges and issues

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.  Domestic violence has a significant impact on the health of those who experience abuse and is a national and global concern. Effective recognition, management and support is now ackno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 62 publications
(76 reference statements)
1
2
0
Order By: Relevance
“…Our finding on differing conceptualisations of VAW reflects previous research that reported a lack of consensus regarding the definition of VAW and terminology used by researchers, practitioners, and research participants [ 35 ]. In the context of global research, the differences in definitions of VAW used by HIC funders, LMIC researchers and REC members were rooted in country-specific socio-political contexts.…”
Section: Discussionsupporting
confidence: 81%
“…Our finding on differing conceptualisations of VAW reflects previous research that reported a lack of consensus regarding the definition of VAW and terminology used by researchers, practitioners, and research participants [ 35 ]. In the context of global research, the differences in definitions of VAW used by HIC funders, LMIC researchers and REC members were rooted in country-specific socio-political contexts.…”
Section: Discussionsupporting
confidence: 81%
“…Strengths of PATH include: recruitment of a sizeable proportion of the eligible women experiencing abuse and seeking help [ 46 ]; successful collaboration with agencies in the DVA sector to deliver a psychological intervention with reasonable fidelity; relatively complete data collection from participants retained in the trial; outcome data from at least one time point after randomisation from 74% of participants; and a nested longitudinal qualitative study (see Evans et al, DOI: 10.1371/journal.pone.0193077 ). The main limitation threatening the internal validity of the trial is the 34% loss of participants 12 months post-intervention, requiring pre-specified imputation of the missing outcome data.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these results, some researchers concluded that health professionals consider to have little information to deal with IPV 58 lack of training about the phenomena, resulting in lower clinical practices integrating IPV screening, difficulties in communicate with victims, and lack of knowledge about how to start the IPV conversation with their patients 59 Findings suggest, for example, that the implicit understanding of the dynamics of violent relationships and the behaviors of the perpetrator of domestic violence are essential components of health care provision to avoid inadvertent inappropriate interactions with women 60 .…”
Section: Prevalence Of Intimate Partner Violencementioning
confidence: 99%